INVESTIGATION AND ANALYSIS OF POWER QUALITY OF SINGLE PHASE, LOW VOLTAGE CONSUMERS IN ADO –EKITI METROPOLIS - Olulope, P.K. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper examines the power quality of Ado-Ekiti metropolis in Ekiti State, Nigeria. The metrics of power quality includes: disturbances such as interruptions, voltage sags, spikes and momentary losses, power harmonics, and voltage unbalances with intrinsic effects on the efficiency and performances on the electric equipment. The necessity for this paper is the fluctuations of voltage supplied to the consumers by the distribution company in Ekiti State. These have significant effects on the power delivered to consumers ‘appliances, quality of their lives and the development of the society at large. The quality of voltage of each consumer in the selected areas were measured with the aid of digital multimeter which was compared with the standard nominal voltage of 240V, voltage deviations were evaluated through the use of standard mathematical equation and linear regression model was employed on the calculated voltage deviation with day and time used as inputs and the voltage deviation as the output. The implementation of the modelling was achieved through the use of Microsoft Excel data tool. The power quality for areas1, 2, 3 for the hours under consideration were poor with respect to R2 range of above 0.5 but better than that area 4 with R2 value of less than 0.5.The results were compared and recommendations were made with the view of improving the power quality in the metropolis.